2021
DOI: 10.1029/2020jd033600
|View full text |Cite
|
Sign up to set email alerts
|

Surface Ozone in the Yangtze River Delta, China: A Synthesis of Basic Features, Meteorological Driving Factors, and Health Impacts

Abstract: Ozone (O 3) is of great importance to air quality in the Yangtze River Delta (YRD) region, China. Focusing on surface O 3 in the YRD, its spatiotemporal characteristics, meteorological driving factors, and health impacts are investigated based on surface O 3 observations in this study. We find that from 2015 to 2019, most cities failed to meet the national standards and O 3 pollution mainly occurred in warm seasons (April-September). Surface O 3 in the YRD increased in the recent years, so did tropospheric col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 62 publications
0
17
0
Order By: Relevance
“…Under adverse weather conditions, O3 pollution episodes occur frequently in the YRD Zhan et al, 2021). Sometimes, O3 pollution can spread throughout the YRD and cause regional O3 pollution, affecting an area of up to 3.5 million square kilometers and harming more than 200 million people.…”
Section: Regional O3 Pollution Episodes In the Yrdmentioning
confidence: 99%
See 1 more Smart Citation
“…Under adverse weather conditions, O3 pollution episodes occur frequently in the YRD Zhan et al, 2021). Sometimes, O3 pollution can spread throughout the YRD and cause regional O3 pollution, affecting an area of up to 3.5 million square kilometers and harming more than 200 million people.…”
Section: Regional O3 Pollution Episodes In the Yrdmentioning
confidence: 99%
“…With dense population and huge energy consumption, this area is now suffering from air quality deterioration (Ding et al, 2013;Xie et al, 2017), especially severe O3 pollution in recent years (Zhan et al, 2020(Zhan et al, , 2021. It was reported that 16 out of the 26 typical cities in the YRD failed to meet the urban national standard for O3 in 2017 (Bulletin on the state of China's ecological environment in 2018, http://www.cleanairchina.org/ product/9943.html), and to make matters worse, O3 concentration has been rising in this region during the past few years (Li et al, 2020;.…”
Section: Introductionmentioning
confidence: 99%
“…The hourly values for each city are calculated by averaging the concentrations at all national monitoring sites in that city. Identification and handling of invalid and lacking data are also manually performed during data processing, following the methods adopted in some previous studies (Xie et al, 2016b;Shu et al, 2016;Gao et al, 2020Gao et al, , 2021Zhan et al, 2020Zhan et al, , 2021. The YRD region consists of 26 typical cities.…”
Section: Ozone Observation Datamentioning
confidence: 99%
“…O 3 pollution is the typical atmospheric environment problem in this region, with a positive trend in O 3 concentration in recent years (Li et al, 2011;Ding et al, 2016;Xu et al, 2018). In previous studies, it was found that high O 3 events generally occur in hot and dry seasons, and are usually related to strong photochemical reactions and high air temperature (Chan and Yao, 2008;Li et al, 2011;Ma et al, 2012;Ding et al, 2013Ding et al, , 2016Xie et al, 2016b;Hu et al, 2016;Pu et al, 2017;Gao et al, 2021;Zhan et al, 2021). The subtropical high also have significant impacts on O 3 concentrations (Shu et al, 2016;Gao et al, 2020;Zhan et al, 2020).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation